Gall bladder duplication with choledochal cyst: A rare entity - Rahul Deo Sharma; Achugatla Sushma; Surendra Singh; Shruti Tewari; Rajeev Redkar (Wolters Kluwer Medknow Publications, 2023)
A 4-year-old male child presented with complaints of abdominal pain and vomiting along with yellowish discoloration of the eyes. Investigations were suggestive of acute pancreatitis and double gall bladder (GB) with dilated common bile duct (CBD) with intraluminal calculi and Type II choledochal cyst. He underwent surgical resection of double GB with dilated CBD with hepatico-docho-jejunostomy. On follow-up, the patient was asymptomatic. Our case highlights the importance of preoperative diagnosis to deal with increased operative difficulty and complications.